Impact of urban factors on road accident in Bangkok, Thailand - Pawinee Iamtrakul; Yongthanit Pimonsathean (International Association of Lowland Technology, 2010)
A decade of road accidents situation in Thailand is a key evidence to call for an in depth understanding for alleviating this complex situation. This study carried out to identify the impact of factors inducing on road accidents in urban area by assessment of the road users' attitude on risk factors. Analytical hierarchy process was applied to determine unsafe component of road environment and the urban factors that significantly contributed to the deterioration of road safety situation. Furthermore, indicators for estimating accident prone area could be also derived in term of mathematical relationships with a visual analysis based on an application of spatial approach. While the specific accident mitigation or safety improvement program can be effortless designed, an inter collaboration among traffic police, health, law, and transport authorities can be gradually initiated in developing a strategy for prevention and sustainable reduction of casualties and deaths on the road.